DESIGNING ONTOLOGY-BASED KNOWLEDGE METADATA FOR THE DOMAIN OF BALINESE KARAWITAN ART IN THE SLENDRO TUNING SYSTEM - Putri, Gusti Agung Maya Anggia; Ariana, Anak Agung Gede Bagus; Suryawan, I Wayan Dharma; Desmayani, Ni Made Mila Rosa; Sarasvananda, Ida Bagus Gede (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The diversity of Balinese karawitan art, particularly in the slendro tuning system, represents a rich cultural heritage that requires preservation efforts through technological innovation. This study aims to design ontology-based metadata for the domain of Balinese karawitan art in the slendro tuning system to provide a systematic knowledge structure. Using the Design Science Research Methodology (DSRM), the research produced an ontology model encompassing key elements such as gambelan (ensemble), golongan (category), fungsi (function), and asal (origin). The ontology was implemented using the Protégé application to facilitate the management, retrieval, and utilization of information digitally. The results show that the designed ontology effectively represents the relationships and characteristics of karawitan elements in detail, supporting the preservation of Balinese cultural arts and paving the way for further advancements in semantic technology. With this knowledge model, it is expected that younger generations will gain a deeper understanding and appreciation of Balinese karawitan art.